2005
DOI: 10.1038/433212a
|View full text |Cite
|
Sign up to set email alerts
|

Transient sexual mimicry leads to fertilization

Abstract: Sexual mimicry among animals is widespread, but does it impart a fertilization advantage in the widely accepted 'sneak-guard' model of sperm competition? Here we describe field results in which a dramatic facultative switch in sexual phenotype by sneaker-male cuttlefish leads to immediate fertilization success, even in the presence of the consort male. These results are surprising, given the high rate at which females reject copulation attempts by males, the strong mate-guarding behaviour of consort males, and… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

3
60
0
4

Year Published

2011
2011
2021
2021

Publication Types

Select...
5
4

Relationship

1
8

Authors

Journals

citations
Cited by 97 publications
(68 citation statements)
references
References 9 publications
3
60
0
4
Order By: Relevance
“…In the wild, small, unpaired males may obtain 535 matings through nonaggressive surreptitious or deceptive tactics and therefore avoid 536 aggressive encounters with large paired males (Hanlon et al, 2005). However, if a small, 537 unpaired male encounters a lone female, he will pair with her and perform aggressive displays 538 to repel other small, unpaired male competitors.…”
Section: Discussion 423mentioning
confidence: 99%
“…In the wild, small, unpaired males may obtain 535 matings through nonaggressive surreptitious or deceptive tactics and therefore avoid 536 aggressive encounters with large paired males (Hanlon et al, 2005). However, if a small, 537 unpaired male encounters a lone female, he will pair with her and perform aggressive displays 538 to repel other small, unpaired male competitors.…”
Section: Discussion 423mentioning
confidence: 99%
“…Many studies have suggested that most cephalopods utilize polyandry, which is where a female mates with multiple males during the spawning season (Hanlon and Messenger, 1996;Hanlon et al, 2005). Previous studies have shown that females not only mate with large size males in a group (the consorts) but also mate with other smaller males (the sneakers) using distinct types of courtship behavior (Hanlon et al, , 2002(Hanlon et al, , 2005Jantzen and Havenhand, 2003b;Naud et al, 2004Naud et al, , 2016Iwata et al, 2005;Wada et al, 2005;Iwata and Sakurai, 2007;Huffard et al, 2008;Sato et al, 2014). These results suggest that males of different sizes may adopt different strategies in order to gain access to females and that females may during the same process choose different males in order to maximize their reproduction success.…”
Section: Introductionmentioning
confidence: 99%
“…Cuttlefish visual signalling systems have received substantial attention, not only because they are spectacular, but the rate at which signals can change is exceptional [8 -10]. This rapid ability to change both the colour and texture of the skin is employed for camouflage and for communication [11]. Thus, the cuttlefish display seems to be a system in which cheating could potentially be rife.…”
Section: Introductionmentioning
confidence: 99%
“…Thus, the cuttlefish display seems to be a system in which cheating could potentially be rife. Observations of the giant cuttlefish (Sepia apama), for example, have shown that small males can mimic females as part of an alternative mating tactic that is successful in nearly half of all attempts [11].…”
Section: Introductionmentioning
confidence: 99%